Distinctive modulation of hepcidin in cancer and its therapeutic relevance - Lin, Feng; Tuffour, Alex; Hao, Guijie; Peprah, Frank Addai; Huang, Aixia; Zhou, Yang; Zhang, Haiqi (Frontiers in Oncology, 2023)
Hepcidin, a short peptide synthesized primarily by hepatocytes in response to increased body iron and inflammation, is a crucial iron regulating factor. Hepcidin regulates intestinal iron absorption and releases iron from macrophages into plasma through a negative iron feedback mechanism. The discovery of hepcidin inspired a torrent of research into iron metabolism and related problems, which have radically altered our understanding of human diseases caused by an excess of iron, an iron deficiency, or an iron disparity. It is critical to decipher how tumor cells manage hepcidin expression for their metabolic requirements because iron is necessary for cell survival, particularly for highly active cells like tumor cells. Studies show that tumor and non-tumor cells express and control hepcidin differently. These variations should be explored to produce potential novel cancer treatments. The ability to regulate hepcidin expression to deprive cancer cells of iron may be a new weapon against cancer cells.